Inversión extranjera directa : determinantes y su contribución a la competitividad: estudio del caso colombiano (2010)
This paper reviews the impact of Direct Foreign Investment-FDI on the main variables affecting competitiveness in the case of Colombia. Through interviews and oficial data this work enters into specific detail on how FDI impacted productivity, innovation, technological transfer, human capital formation and competition during the current century finding that inward investment, which concentrated mainly on natural resources, has had limited impact on variables determining Colombian competitiveness.